Do depression, fatigue, and body esteem influence premenstrual symptoms in nursing students? - Eun Joo Lee; Seung Kyoung Yang (Korean Society of Women Health Nursing, 2020)
Purpose The purpose of this study was to investigate factors affecting premenstrual symptoms among nursing students, focusing on depression, fatigue, and body esteem. Methods The participants were 145 nursing students at a university located in Changwon, Korea. Data were collected from November 2 to November 30, 2019 using self-reported structured questionnaires, and analyzed using descriptive statistics, independent t-test, analysis of variance, Pearson correlation coefficients, and multiple regression analysis. Results The mean item score for premenstrual symptoms was 2.52±0.92, indicating a low level. The mean score for depression was 16.05±7.72, and 15.2% of participants were found to be moderately depressed and 9.7% severely depressed. The mean item score for fatigue was 4.84±0.84, indicating a moderate level, and body esteem was 2.94±0.44, indicating a moderate level. The premenstrual symptoms of nursing students showed a statistically significant correlation with depression (r=-.58, p<.001), fatigue (r=.33, p<.001), and body esteem (r=-.28, p<.001). Factors impacting premenstrual symptoms of nursing students were depression (β=.47, p<.001), dysmenorrhea (β=-.18, p=.009), menstrual cycle irregularity (β=.17, p=.013), and body esteem (β=-.14, p=.038). The total explanatory power of these variables was 41.0%. Conclusion Findings from this sample of nursing students suggest that intervention programs to relieve premenstrual symptoms should focus on depression, menstrual cycle regularity, dysmenorrhea, and body esteem.